Using Linked Health Service Data in The Evaluation of Innovative Models of Healthcare - Rebecca Kwok-yee Pang; Velandai Srikanth; Gary Braun; Fergus McGee; Belinda Berry; Iain Edwards; Ruth Azzopardi; Nadine Andrew (International Journal of Population Data Science, 2020)
Introduction Ageing populations place considerable burden on healthcare systems. Innovative methods to implement and evaluate new care models to reduce unwarranted hospital presentations, are needed.